WORKSHOP DIGITAL PRESENTATION KEPADA SANTRIWATI PONDOK PESANTREN ROOIHATUL JANNAH SUKOHARJO DALAM MENINGKATKAN SKILL PRESENTASI - Dani Kurniawan (WASATHON Jurnal Pengabdian Masyarakat, 2026)
Abstract The advancement of digital technology has made communication applications such as Zoom and Google Meet essential tools in the fields of education and da'wah. However, observations show that female students (santriwati) at the Rooihatul Jannah Islamic Boarding School in Sukoharjo lack adequate skills in utilizing digital tools for presentations. This highlights the urgency of conducting a community service activity in the form of a Digital Presentation Workshop. The objective of this workshop was to enhance students’ abilities in creating and delivering digital presentations effectively. The workshop was held on Sunday, May 28, with approximately 31 participants. Evaluation results showed significant improvements, including a 20% increase in self-confidence, a 10% reduction in stage fright and confusion during presentations, as well as a 30% improvement in Canva design skills and Zoom operation. The outcomes of this community service activity will be published in the Washaton community service journal. Keyword: Digital Presentation; Skill; Zoom; Canva.